2021
DOI: 10.20524/aog.2021.0684
|View full text |Cite
|
Sign up to set email alerts
|

Radiation proctitis: predictors of mortality and inpatient outcomes in the United States

Abstract: Background We aimed to evaluate the characteristics of hospitalizations for radiation proctitis (RP). Methods The National Inpatient Sample (NIS) was analyzed to identify RP hospitalizations for 2016 and 2017. Outcomes included mortality, predictors of mortality, mean length of stay (LOS), mean total hospital cost (THC), and numerous system-based complications. Results We identified 16,810 adult hospitalizations for RP. On admission, an initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…As per the literature from Dahiya (17) , older patients (mean age 72.3 ± 0.5 years) have been shown to be prone to hospitalizations due to radiation proctitis. Our study also indicated that older patients (≥ 54 years old) had a greater risk of hemorrhagic CRP.…”
Section: Discussionmentioning
confidence: 73%
“…As per the literature from Dahiya (17) , older patients (mean age 72.3 ± 0.5 years) have been shown to be prone to hospitalizations due to radiation proctitis. Our study also indicated that older patients (≥ 54 years old) had a greater risk of hemorrhagic CRP.…”
Section: Discussionmentioning
confidence: 73%